Analisis Kepadatan Kendaraan Jalan Pecangaan - Kedung Kabupaten Jepara - Ariyanto Ariyanto; Decky Rochmanto; Achmad Rafiul Umam; Khotibul Umam (Reviews in Civil Engineering, 2021)
The vehicle density analysis survey is a survey conducted with the aim of knowing the size of the density and also the obstacle factors on the analyzed road. At the Bugel Kedung Jepara T-junction, the survey point is the middle point of the current conflict, or the meeting point of two heavy vehicle flows, from the flow of vehicles originating from the traffic light at the junction of Pecangaan Walisongo Jepara and the flow of vehicles originating from the Mantingan Jepara red light intersection. The survey results on Thursday and Sunday, on Thursday can represent the effective working day, the degree of saturation is 0.16 pcu / hour, 2 seconds delay for a total of 5796 vehicles, the side friction is 223.8, indicating that the level of side resistance (L) low. The results of the calculation of vehicle density using the Greenshields Method show that after analyzing the survey results at point IV, the densest point is at point V, which is at the red light junction of Walisongo, Pecangaan Jepara, which occurs during the peak hours of the afternoon at 16.00 - 17.00 WIB. Vehicle density = 36.31 pcu / hour and the level of road service (B) with a LOS analysis value of 0.31 including good. To minimize the occurrence of conflicts and accidents, at each I-V survey point it is necessary to add a caution sign or additional signs on each road segment